Modeling Of Biopolymerization Process Using First Principle Model And Bootstrap Re-Sampling Neural Network - Noor, Rabiatul 'Adawiah Mat (2011)

(untitled)
The emergence of the environmental issues such as green house and global warming have triggered scientists and researchers to create new materials that can cope both environmental and humanity needs i.e. biopolymer. Biopolymer quality assesses by its molecular weight. Apparently, there is no online measurement for molecular weight measurement. Therefore, in this study models are developed to mimic the real process using a reliable modeling tool such as neural networks. First principle model also become one of the most applied methods to model a process other than using a modeling tool such as neural network.